[PP.12.02] IMPAIRED FLOW-INDUCED DILATION OF MIDDLE CEREBRAL ARTERIES OF SPRAGUE-DAWLEY RATS ON A HIGH SALT DIET IS ASSOCIATED WITH REDUCED ANTIOXIDANT CAPACITY AND RESTORED BY TEMPOL IN VIVO. (September 2016) - Drenjancevic, I.; Cosic, A.; Jukic, I.
Abstract : Objective: Previously, we demonstrated impaired flow-induced dilatation (FID) of middle cerebral artery (MCA) in Sprague-Dawley (SD) rats fed 1 week high salt (HS) diet compared to rats on a low salt (LS) diet. Superoxide scavenger TEMPOL in vitro restored FID in HS group. The aim of this study was to assess if TEMPOL in vivo given simultaneously with HS or LS diet affects vascular function and the level of oxidative stress. Design and method: Healthy male 11-weeks old SD rats were divided in LS-TEMPOL group fed 0.4%NaCl chow and HS-TEMPOL group fed 4%NaCl chow. Simultaneously, both groups consumed TEMPOL (1 mM) in tap water for 1 week. After diet protocol, rats were anesthetized with ketamin-chloride (75 mg/kg) and midazolam (2.5 mg/kg) and than sacrificed. Response to stepwise increase in pressure (δ10-δ100 mmHg) (FID) was measured in isolated and cannulated MCA (N = 10–16). mRNA expression (N = 5–7) of Cu/ZnSOD, MnSOD, ecSOD, catalase (CAT), inducible nitric oxide synthase (iNOS) and endothelial nitric oxide synthase (eNOS) from brain blood vessels was determined by real-time quantitative PCR (BioRad CFX96). Indicators of oxidative stress Thiobarbituric Acid Reactive Substances (TBARS) and antioxidant capacity (FRAP) were measured from arterial blood. All experimental procedures conformed to the European Guidelines for the Care and Use of Laboratory Animals (directive 86/609) and were approved by the local Ethical Committee. Results: There was no significant differences in the FID response between investigated groups (p > 0.05). mRNA expression of antioxidative enzymes MnSOD and CAT and of iNOSand eNOS was significantly decreased in HS+TEMPOL group compared to LS+TEMPOL. TBARS was significantly higher in rats on HS+TEMPOL diet compared to LS+TEMPOL group without significant changes of plasma antioxidant capacity (FRAP). Expression of Cu/ZnSOD and ecSOD did not changed significantly. Conclusions: TEMPOL restored the function of blood vessels and prevented the harmful effects of salt on FID by decreasing the superoxide level, subsequently increasing the NO level, despite lower NOS-isoforms expression. It is possible that TEMPOL generates an additional amount of H2O2 which cannot be removed due to decreased catalase expression and therefore increases TBARS in HS+TEMPOL group.